Biocompatible PLA/PCL blends nanocomposites doped with nanographite: Physico-chemical, and thermal behaviour - Qader, Ibrahim Nazem; PekdemIr, Mustafa Ersin; Coskun, Meltem; Kanca, Muhammed Sait; Kok, Mediha; Dagdelen, Fethi (Springer, 2022)
There is a great interest in nano-graphite due to its wide application in nanotechnology and important physical properties. Nanocomposites based on polymers and blends are important in the development of traditional polymers and in improving their usage areas. The aim of this study is to improve physico-chemical, and thermal behavior of poly(lactic acid) / poly(epsilon-caprolactone) (PLA/ PCL) blend by doping nano-graphite (NG) with different amounts and make the characterization of these nano-composites. It was observed that NG affected the temperature at which nanocomposites decompose. Also, the nanoparticles incorporated in the polymer blend become locked between the polymer filaments, speeding up the composites' decomposition. NG has significantly higher melting and evaporation temperature than PLA and PCL, so more residues were left as the quantity of NG rose. There was no significant change in the T-g and T-m peaks in the DSC experiment due to the inclusion of NG. While the NG particles raised the enthalpy of phase transition in general. The sharpness of the XRD peaks and the crystallinity of the nanocomposites both enhanced as the amount of NG in the blend was increased. Shape memory has been demonstrated to be a remarkable characteristic of thermos-sensitive PLA / PCL blend. Although the trained nanocomposite recovered most of its predetermined shape, increasing NG concentration in the composite may diminish its recovery behavior because.
Keywords: Nano graphite; Poly(lactic acid); Shape memory polymer; Nanocomposite